Mobile health messaging service and helpdesk for South African mothers (MomConnect): history, successes and challenges. (24th April 2018) - Barron, Peter; Peter, Joanne; LeFevre, Amnesty E; Sebidi, Jane; Bekker, Marcha; Allen, Robert; Parsons, Annie Neo; Benjamin, Peter; Pillay, Yogan
Abstract : MomConnect is a flagship programme of the South African National Department of Health that has reached over 1.5 million pregnant women. Using mobile technology, MomConnect provides pregnant and postpartum women with twice-weekly health information text messages as well as access to a helpdesk for patient queries and feedback. In just 3 years, MomConnect has been taken to scale to reach over 95% of public health facilities and has reached 63% of all pregnant women attending their first antenatal appointment. The helpdesk has received over 300 000 queries at an average of 250 per day from 6% of MomConnect users. The service is entirely free to its users. The rapid deployment of MomConnect has been facilitated by strong government leadership, and an ecosystem of mobile health implementers who had experience of much of the content and technology required. An early decision to design MomConnect for universal coverage has required the use of text-based technologies (short messaging service and Unstructured Supplementary Service Data) that are accessible via even the most basic mobile phones, but cumbersome to use and costly at scale. Unlike previous mobile messaging services in South Africa, MomConnect collects the user's identification number and facility code during registration, enabling future linkages with other health and population databases and geolocated feedback. MomConnect has catalysed additional efforts to strengthen South Africa's digital health architecture. The rapid growth in smartphone penetration presents new opportunities to reduce costs, increase real-time data collection and expand the reach and scope of MomConnect to serve health workers and other patient groups.